Parent–child genetic testing for familial hypercholesterolaemia in an Australian context. (6th April 2018) - Pang, Jing; Martin, Andrew C; Bates, Timothy R; Hooper, Amanda J; Bell, Damon A; Burnett, John R; Norman, Richard; Watts, Gerald F
Abstract : Aim: The aim of this study was to evaluate the clinical outcome of parent–child testing for familial hypercholesterolaemia (FH) employing genetic testing and the likely additional cost of treating each child. Methods: Parent–child testing for gene variants causative of FH was carried out according to Australian guidelines. The number of new cases detected, the low‐density lipoprotein (LDL)‐cholesterol that best predicted a mutation and the proportional reduction in LDL‐cholesterol following statin treatment was evaluated. Treatment costs were calculated as the cost per mmol/L reduction in LDL‐cholesterol. Results: A total of 126 adult patients, known to have a pathogenic mutation causative of FH, and their children were studied. From 244 children identified, 148 (60.7%) were genetically screened; 84 children were identified as mutative positive (M+) and 64 as mutative negative. Six of the M+ children were already on statin treatment; 40 were subsequently treated with low‐dose statins, with LDL‐cholesterol falling significantly by 38% ( P < 0.001). The estimated cost per mmol/L reduction of LDL‐cholesterol of a child receiving statins from ages 10 to 18 years is AU1361, which can potentially be cost‐effective. An LDL‐cholesterol threshold of 3.5 mmol/L had a sensitivity of 92.8% and specificity of 96.6% for the detection of a mutation. Conclusion: Genetic testing of children of affected parents with FH is an effective means of detecting new cases of FH. Cascade testing can enable early statin therapy with significant reductions in LDL‐cholesterol concentration.